Musiikin tuotannon ja teknologian muuttuvia suhteita - Kolme näkökulmaa tuottajan toimijuuden rakentumiseen - Tuomas Auvinen (Suomen Musiikkitieteellinen seura, 2022)
This article explores the ways in which the producer’s agency is formed through technological practices with respect to authorship. Through three distinct ethnographic case studies on music production projects in pop music, in classical and in rock, the article seeks to answer the questions: how does music technology as the central enabling and limiting structure of music production influence the producer’s agency with respect to their authorship, and how does the producer use music technology in order to construct their agency during the music production process. Perspectives on technological practices and social interactions are of central importance here.
Agency here refers to the individual or collective ability to move within a structure (Taylor 2001). The goal of this article is to take a micro level perspective on how agency is formed in the studio environment, which is the central setting of music production. By investigating the producer’s activities in the studio, one of the goals of this article is to discuss the ways in which producers influence the sonic result of music production through technological and social interactions without gaining authorship with respect to the musical work.
This article contributes to the scholarly discussions of the producer’s role and the relationship between music technology and agency in music production. It falls into the confines of the academic fields of cultural study of music production and cultural study of music technology. The underlying argument in the article is that our current copyright law provides a shallow understanding of what is important in the sonic result of music production. Through their technological activities in the studio, producers always have agency even if they don’t have authorship.